Novel arc-shaped ligaments to enhance energy absorption capabilities of re-entrant anti-trichiral structures - Zhang, Ee Teng (2022)
In this study, novel re-entrant anti-trichiral (REAT) structures with arc-shaped ligaments are proposed to enhance both the elastic modulus and energy absorption capabilities through both experimental and numerical approaches. By first replacing straight ligaments with curved ligaments, unique deformation patterns are introduced through the rotation of cylinders, contact interaction between cylinder and ligaments, as well as petal-like cell interactions. Quasi-static compression reveals the effect of curvature along ligaments and their directions on the Young's modulus, Poisson's ratio, plateau stress and specific energy absorption capabilities. The primary finding is an improvement of up to eight times in normalised Young's modulus and up to four times in specific energy absorption (SEA) with the introduction of combined curved ligaments (Dc + Uc) design. In addition, parametric studies on geometrical parameters of ligament curvature and cylinder diameter shows significant influence over mechanical properties and deformation patterns. The present study sheds light on the development of novel REAT honeycombs that can be achieved through simple ligament modifications and combinational designs.